PENGAMBILAN KEPUTUSAN UNTUK MEMAKAI NARKOBA PADA DEWASA AWAL YANG PERNAH MENEMPUH PENDIDIKAN DI PONDOK PESANTREN - Kurrota Aini; Anna Armeini Rangkuti (Journal of Research and Measurement in Psychology, 2014)
This study aims to determine the background factors of decision making to use drugs on young adult ever studied in boarding school.The approach used in this study is a qualitative approach with a qualitative case study approach. Subjects in this study amounted to 2 drug user after graduate from boarding school and from different boarding school, one from traditional boarding school and one from modern boarding school, they are 23 years old. Data collection techniques used were interviews. Data were analyzed using qualitative data analysis techniques and techniques of data validity checks using triangulation. These results indicatethatthere are sixfactors thataffect the subjectinmaking decisionsthatarepreferences, values, beliefs, emotions, and action circumstances. Of the six factors are the most influential factor that circumstances. Environment and the influence of friends is part of circumstances factor that affect both subjects. Keyword: Decision Making, Young Adult, Drugs, Boarding School